KONVERSI LAHAN TANAMAN KARET KE TANAMAN KELAPA SAWIT DI KENAGARIAN INDERAPURA TIMUR KECAMATAN PANCUNG SOAL KABUPATEN PESISIR SELATAN - Yelmi, Idel Pina; Rianto, Slamet; Thesiwati, Aslan Sari (Pendidikan Geografi, 2013)
The purposes of this research to knew the conversion melodious of rubber plants into Oil Palm plants in Kenagarian Indrapura Timur kecamatan Pancung Soal Kabupaten Pesisir Selatan. This research, the researcher used descriptive comparativeThe total population of this research was all family head of farmer to do conversion rubber plants into oil palm Â plants in Kenagarian Indrapura Timur Kecamatan Pancung Soal Kabupaten Pesisir Selatan 50 family head. The sample of this research used total sampling. The total sampling was all of population to become a sample in Kenagarian Indrapura Timur Kecamatan Pancung Soal Kabupaten Pesisir Selatan 50 family head.The result of this research, the researcher found out the conversion of rubber plants into oil palm plants. The first, the cost production of rubber plants was low compare with the cost production of coconut plants. The cause was large of land oil palm plants more than rubber plants. It was not barrier of farmer to conversion of rubber plants into oil palm plants. The second, the result of rubber plants was very high balance to the result of oil palm plants. Therefore, the plants of oil palm were give promise economy of society. The last, there were not process to selling of rubber plants and oil palm in Kenagarian Indrapura Timur Kecamatan Pancung Soal Kabupaten Pesisir Selatan. Thus, the farmer was not need to learned process of selling oil palm plants